Financial Inclusion as a Determinant of Short-Term Liquidity Risk in Tunisia's Banking Sector - Mouna, HAMZA; Younes, BOUJELBENE (Journal of Posthumanism, 2025)
This paper empirically examines the effect of financial inclusion on the resilience to short-term liquidity stress of commercial Tunisian banks using data for the period 2010–2021. We utilize the two-step generalized method of moments (GMM) estimator. We mainly draw the inference that financial inclusion and bank profitability have a positive influence on bank liquidity risk resilience. We also give proof that the bank size has a negative impact. Nevertheless, bank capital and economic growth have no impact. Eventually, the findings support the view that bank resilience to short-term liquidity shocks can be enhanced by a stable macroeconomic environment. According to the author's current knowledge, no previous empirical research has been carried out in the banking sector in Tunisia in which the impact of financial inclusion on bank resilience to liquidity stress is examined